MAKING OF HELICOPTER MODELS WITH POLYGONAL MODELING TECHNIQUES IN MABUR MOTOR GAME WITH 3D BLENDER - Atmojo, Bayu Dwi (Compiler, 2018)
Currently 3D modeling has been many developed and widely applied to various fields of industry, one of the modelling techniques is a polygonal modelling technique that can be applied to games with 3D graphics. Games that are currently considered as some entertainment media can only be used as entertainment media to train agility and concentration by making it an interactive game with good visuals. The manufacture of 3D helicopter model aims to produce helicopter models that can be applied to the game Motor Mabur. From the test results of Motor Mabur game that is uploaded on the game site itch.io got the number of views 84, download 30, rating 4, collections 1, comment 10, impressions 110 and ctr 0.91 %.